The obesity paradox in patients with major burn injuries: a single tertiary burn centre review - Michaela Pollock; Eldho Paul; Cheng Hean Lo (Australasian Journal of Plastic Surgery)
**Introduction:** The obesity paradox is a phenomenon described in medical literature where overweight and obese patients have improved survival and better health outcomes. The obesity paradox is of curiosity to many clinicians as the general consensus in medicine has been that a higher body mass index results in poorer health outcomes in both medical and surgical conditions. The aim of this study is to determine whether the obesity paradox exists in our patients with major burn injuries. To our knowledge, this has not been previously investigated in the Australian major burn population.